STUDIES ON PESTICIDE REMOVING EFFICACY AND ANTIBACTERIAL ACTIVITY OF DHATHRI EAT PURE NATURAL VEGETABLE CLEANER FOR FRUITS AND VEGETABLES - Rajeshkumar, Appukuttan; Sajikumar, Sahadevan; Jeyaram, Chitra; Ramasamy, *Maniramakrishnan Santhana (International Journal of Ayurveda and Pharma Research, 2017)
Fruits and vegetables are highly nutritious and form as key food commodity in the human consumption. They are highly perishable due to their low shelf life. These food commodities are reported to be contaminated with microbes and health hazardous chemicals such as pesticides. Hence, it is very necessary to remove the pesticides and prevent the microbial contamination of fruits and vegetables without changing its nutritional value. For this purpose Dhathri Eat Pure Natural Vegetable Cleaner (DEPNVC) have been used to wash out the pesticides along with prevention of microbial contamination. The present study was performed to study the pesticide removing efficiency and antimicrobial activity against the food borne microbial pathogens. Dhathri Eat Pure Natural Vegetable Cleaner contains natural ingredients such as Coconut vinegar, Neem (Azadirachta indica), Turmeric (Curcuma longa). The HPTLC studies were also performed to determine the ingredients of DEPNVC. The results shown that DEPNVC has the 75 % (Organo Phosphorous) 90% (organo chlorines) of pesticides and the dose dependent antibacterial activity with mean zone of inhibition was observed as 11.63 ± 3.03 mm.